MAKNA KONOTATIF DALAM TEKS ULASAN CERPEN DALAM MATA KULIAH SEMANTIK MAHASISWA BAHASA INDONESIA SEMESTER III UNIVERSITAS MUHAMMAD YAMIN SOLOK TAHUN PELAJARAN 2017/2018 - SHAUMIA, DIAN (Inovasi Pendidikan, 2019)
This research is motivated because connotative meaning is not only used in society only, in the text of the short story used the language is very diverse. In writing the text of the short story students only write based on ideas and ideas alone regardless of the use of words and meaning of words contained in the text of the short story reviews. Actually the words written by the students contain a lot of meaning. This study aims to describe the connotative meaning in the text of the students of class education study. This type of research is a qualitative research that produces written data of connotative meanings in the text of students of class education study . The method used in this research is descriptive method that is describe connotative meaning in the text of student class education. The data collection technique is done by the teacher explaining the text material of the short story and connotative meaning, the teacher distributes the short story sheet which will be reviewed, the teacher assigns the students to make the review text, the teacher collects the students work, and the researcher asks the students Indonesia. The steps taken in analyzing the data in this study is, reading the text of the students' short story reviews, underlining words that include connotative meanings by coding in accordance with research instruments, classifying data into tables contained in research instruments, analyzing connotative meanings used by students, and summarizes the results of connotative meaning analysis. Based on the research result, it is concluded that there are 14 connotative meanings. Keywords: connotative meanings, short story text.